Risk factors for diabetic retinopathy: a case-control study - Pratiksha Nathani; Pratik R. Kharat; Satish Wadde (Journal of the Egyptian Ophthalmological Society)
Purpose To emphasize the severity of the issue, it is crucial to recognize that diabetic retinopathy (DR) is not only the biggest contributor to blindness in India, but it is also becoming increasingly prevalent with each passing day. This study offers information from a matched case-control study conducted in an Indian tertiary care hospital on several risk factors for DR. The objective of the investigation is to identify the primary diabetes mellitus (DM) risk factors and the amount by which they influence diabetes pathogenesis. Methods The outpatient and inpatient departments participated in a matched research study. Diabetics with DR were included among the patients, while diabetics without DR were included in the controls. Before performing structured interviews, a total of 252 people (126 cases and 126 controls) were recruited and matched for age (±2 years) and sex. Results The average age in the DR and non-DR categories was 63.7 9.5 years and 63.3 10.4 years, respectively. Smoke (OR=1.92, P=0.02), alcoholism (OR=2.62, P=0.03), a poor diet (OR=2.72, P=0.0008), nonadherence to dietary advice (OR=4.41, P=0.0001), other microvascular disorders (OR=3.79, P=0.0001), dyslipidaemia (OR=1.85, P=0.0), and hypertension (OR=5.91, P=0.0001). Drug abnormalities (adjusted odds ratio (AOR)=7.89, P=0.0001) and hypertension (AOR=1.16, P=0.0001) were indicated as risk factors for the development of DR in multivariate regression research. Conclusion According to our findings, DM with inconsistent anti-diabetic drug use and hypertension are more likely to acquire DR. Modifiable risk factors for DR include insulin, physical inactivity, dyslipidemia, alcoholism, and smoking. With the increasing frequency of DR educating DM about lifestyle changes that may minimize their risk of developing DR is more critical than ever.